INTELLIGENT CHATBOT FOR ENHANCING ACADEMIC CONSULTATION SERVICES IN VOCATIONAL SCHOOLS USING NATURAL LANGUAGE PROCESSING - Yolanda Estefania Hasibuan; Ahmad Zakir (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
Academic consultation is essential in supporting students’ learning, personal development, and career planning in vocational schools. Traditional consultation services, however, often face challenges such as limited advisor availability, time constraints, and inefficient record-keeping, which reduce service effectiveness and accessibility. This study proposes the development of an intelligent chatbot to enhance academic consultation services at Vocational High School (SMK) Multi Karya using Natural Language Processing (NLP). The chatbot serves as a virtual assistant capable of understanding students’ queries in natural language, providing real-time guidance, and recording consultation history for further analysis. The system integrates modules for user authentication, account management, class and subject management, schedule organization, consultation history, and interactive chat. Evaluation results demonstrate that the chatbot improves accessibility by enabling students to consult anytime, enhances efficiency through automation of administrative tasks, and delivers context-aware, personalized responses. Interaction logs allow administrators to monitor and evaluate service quality, facilitating data-driven improvements. Despite limitations in handling ambiguous or complex queries, and the need to address ethical considerations such as data privacy and algorithmic bias, the chatbot represents a practical and innovative solution for modernizing academic consultation in vocational education. This study highlights the potential of AI-driven chatbots to provide inclusive, responsive, and effective student support, establishing a foundation for future advancements in educational technology and intelligent learning systems.